1963
DOI: 10.3181/00379727-114-28808
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Prolonged Effects of Hydrocortisone on the Free Amino Acids of Rat Skeletal Muscle.

Abstract: terized by marked degeneration and necrosis of monolayer cultures. Multiple small foci of degeneration and necrosis were observed as early as 16 hours post inoculation. These focal areas enlarged until most cells were affected by 72 hours after exposure to the virus. ' Early cellular changes consisted of rounding of cells with condensation of the cytoplasm. These changes were often accompanied by vacuolization or ballooning of the cytoplasm and shrinkage of the nucleus. Next, necrosis, as evidenced by pyknosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

1966
1966
1990
1990

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 0 publications
3
6
0
Order By: Relevance
“…Nevertheless, examination of their data reveals higher mean plasma levels during cortisol treatment only in the case of alanine, at each of three time periods examined (24 h, 1-3 days, and 3-5 days). In acute experiments, a single dose of glucocorticoid has been observed to increase plasma alanine concentration in children (29) and in rats (30). The present data demonstrate a specific elevation in plasmia alanine after 3 days of dexamethasone treatment.…”
Section: Discussionsupporting
confidence: 63%
“…Nevertheless, examination of their data reveals higher mean plasma levels during cortisol treatment only in the case of alanine, at each of three time periods examined (24 h, 1-3 days, and 3-5 days). In acute experiments, a single dose of glucocorticoid has been observed to increase plasma alanine concentration in children (29) and in rats (30). The present data demonstrate a specific elevation in plasmia alanine after 3 days of dexamethasone treatment.…”
Section: Discussionsupporting
confidence: 63%
“…The placenta is an active metabolic organ with significant oxygen requirements (3) and involved in the synthesis of large amounts of protein. Similar amino acid concentrations have been reported in other active metabolic organs such as liver, brain, and muscle (1, 14,15).…”
Section: L-leucine L-aspartic Acid Discussionsupporting
confidence: 55%
“…Previous studies suggested that these differences appear to be time-related (36 The initial elevation induced by glucocorticoids is con-sistelit with an increase in amino acid mobilization from the peripheral tissues (37). A feasible explanation for the subsequent depression is the decreased release of amino acids from muscle (the body's principal protein store) coincident with the secondary hyperinsulinemia (38) that developed after glucocorticoid administration.…”
Section: Resultsmentioning
confidence: 99%